Limiting environmental reporting flexibility: investor judgment based on the EU taxonomy - Sandra Chrzan; Christiane Pott (Review of Quantitative Finance and Accounting, 2024)
Abstract This experimental research investigates the effect of different types of environmental information on investor judgment. By examining three experimental cases varying the level of environmental disclosure, we evaluate the investment judgments of professional (Study 1) and private German investors (Study 2). Primarily, we investigate whether traditional, commonly disclosed environmental information affects investor judgments. Furthermore, we explore the effects of linking non-financial reporting elements to quantitative financial measures through the EU taxonomy by adding taxonomy indicators. Specifically, we operationalized the case where companies fall into a category of poor environmental performance by taxonomy classification. We find that only traditional environmental disclosure in combination with standardized taxonomy-aligned information (below average), influences the investment judgment. However, professional investors exhibit a significantly negative response, while private investors show a significantly positive reaction when constraining reporting flexibility through the inclusion of standardized taxonomy measures with poor performance. Consequently, we conclude that the connection between non-financial reporting elements and quantitative standardized financial measures enhances transparency for professional investors. Private investors, on the other hand, reward additional taxonomy-aligned environmental information irrespective of its content. This implies that environmental information generally conveys positive signals to private investors, but uncertainty in investment judgment can be assumed.
Keywords: 330; EU taxonomy; Investment judgment; Non-financial disclosure; CSR reporting; ESG investment; Experimental study